1990
DOI: 10.1016/0167-2681(90)90006-y
|View full text |Cite
|
Sign up to set email alerts
|

The acquisition of technology and small firms by large firms

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
109
0
6

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(121 citation statements)
references
References 5 publications
6
109
0
6
Order By: Relevance
“…By technological diversification, a firm can exploit novel combinations of its internal technologies in combination with unfamiliar external technologies and create new innovation value through discoveries in related areas (Granstrand et al, 2007;Garcia-Vega, 2006). If it has a diversified knowledge base, a firm can achieve a great level of cross-fertilization between different yet related technologies (Granstrand & Sjölander, 1990;Garcia-Vega, 2006). A diversified knowledge base demonstrates a firm's strong capabilities to recognize and mobilize the real option value of knowledge embedded in the licensed technologies and further allow itself to establish "architectural competence" by integrating dispersed knowledge from various sources into a coherent whole (Henderson & Cockburn, 1996;McGrath, Macmillan, & Venkataraman, 1995).…”
Section: H1: the Breadth Of A Firm's External Technological Resourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…By technological diversification, a firm can exploit novel combinations of its internal technologies in combination with unfamiliar external technologies and create new innovation value through discoveries in related areas (Granstrand et al, 2007;Garcia-Vega, 2006). If it has a diversified knowledge base, a firm can achieve a great level of cross-fertilization between different yet related technologies (Granstrand & Sjölander, 1990;Garcia-Vega, 2006). A diversified knowledge base demonstrates a firm's strong capabilities to recognize and mobilize the real option value of knowledge embedded in the licensed technologies and further allow itself to establish "architectural competence" by integrating dispersed knowledge from various sources into a coherent whole (Henderson & Cockburn, 1996;McGrath, Macmillan, & Venkataraman, 1995).…”
Section: H1: the Breadth Of A Firm's External Technological Resourcesmentioning
confidence: 99%
“…Therefore, we use the average number, instead of the total number, of unique patent classes to avoid a potentially high correlation between the number of licensed patents and the number of unique classes. Similar to prior work, we measure this variable by counting the average number of unique patent classes (using the 4-digit patent classification code for Chinese invention and utility types of patent) of a firm's yearly in-licensed patents (Granstrand & Sjölander, 1990;Wang & von Tunzelmann, 2000;Zhang & Baden-Fuller, 2010). …”
Section: Independent Variablesmentioning
confidence: 99%
“…Indeed, we observe a significant amount of interfirm technology transfers, ranging from joint ventures and licensing to outright acquisitions of innovations. 17 However, it can be shown that our identified mechanism is still valid as long as there is bidding competition over the innovation. The reason is that the entrepreneur then exerts similar negative externalities as in the case of entry, and globalization affects these externalities in a similar fashion.…”
Section: Entrepreneurial Innovations For Salementioning
confidence: 94%
“…18 16 For a proof, see working paper version Douhan, Norbäck and Persson (2009). 17 Granstrand and Sjölander (1990) present evidence from Sweden and Hall, Berndt and Levin (1990) present evidence from the US of firms acquiring innovative targets to gain access to their technologies.…”
Section: Entrepreneurial Innovations For Salementioning
confidence: 99%
“…Pour surmonter ces difficultés, leurs dirigeants-propriétaires n'hésitent pas à les céder à des firmes de taille plus importante qui, grâce à un transfert de ressources et de compétences, peuvent les aider à se repositionner dans cette chaîne de production verticale (Teece, 1987 ;Shelton, 1988 ;Granstrand et Sjölander, 1990 ;Courlet et Sanson, 1992 ;Hyun, 1994).…”
Section: Introductionunclassified